2006
DOI: 10.1002/eat.20238
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and body image in adult outpatients with binge eating disorder

Abstract: Alexithymia was associated with more severe BED. Individuals with alexithymia and BED exhibited significantly poorer appearance evaluation and body satisfaction as well as higher depressive symptoms than individuals without alexithymia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 62 publications
6
66
2
9
Order By: Relevance
“…There is consistent evidence that alexithymia is elevated in people with eating disorders (Beales & Dolton, 2000;Carano et al, 2006;Cochrane, Brewerton, Wilson, & Hodges, 1993;De Panfilis, Salvatore, Avanzini, Gariboldi, & Maggini, 2001;Kessler, Schwarze, Filipic, Traue, & von Wietersheim, 2006;Mazzeo & Espelage, 2002;Pinaquy, Chabrol, Simon, Louvet, & Barbe, 2003;ZonneyvilleBender, van Goozen, Cohen-Kettenis, van Elburg, & van Engeland, 2002;Zonnevylle-Bender et al, 2004), problematic gambling (Lumley & Roby, 1995;Parker, Wood, Bond, & Shaughnessy, 2005), and alcohol and drug abuse or dependence (El Rasheed, 2001;Haviland, Hendryx, Shaw, & Henry, 1994;Kauhanen, Julkunen, & Salonen, 1992), although perhaps not cigarette smoking and nicotine dependence (Lumley, Downey, Stettner, Wehmer, & Pomerleau, 1994). One comprehensive study found that compared with controls, patients with eating disorders or alcohol-or drugrelated disorders had similar, high levels of alexithymia, and a path analysis suggested that alexithymia predicted depression that predicted the addictive behavior in these disorders (Speranza et al, 2004).…”
Section: Does Alexithymia Contribute To Unhealthy Behavior?mentioning
confidence: 94%
“…There is consistent evidence that alexithymia is elevated in people with eating disorders (Beales & Dolton, 2000;Carano et al, 2006;Cochrane, Brewerton, Wilson, & Hodges, 1993;De Panfilis, Salvatore, Avanzini, Gariboldi, & Maggini, 2001;Kessler, Schwarze, Filipic, Traue, & von Wietersheim, 2006;Mazzeo & Espelage, 2002;Pinaquy, Chabrol, Simon, Louvet, & Barbe, 2003;ZonneyvilleBender, van Goozen, Cohen-Kettenis, van Elburg, & van Engeland, 2002;Zonnevylle-Bender et al, 2004), problematic gambling (Lumley & Roby, 1995;Parker, Wood, Bond, & Shaughnessy, 2005), and alcohol and drug abuse or dependence (El Rasheed, 2001;Haviland, Hendryx, Shaw, & Henry, 1994;Kauhanen, Julkunen, & Salonen, 1992), although perhaps not cigarette smoking and nicotine dependence (Lumley, Downey, Stettner, Wehmer, & Pomerleau, 1994). One comprehensive study found that compared with controls, patients with eating disorders or alcohol-or drugrelated disorders had similar, high levels of alexithymia, and a path analysis suggested that alexithymia predicted depression that predicted the addictive behavior in these disorders (Speranza et al, 2004).…”
Section: Does Alexithymia Contribute To Unhealthy Behavior?mentioning
confidence: 94%
“…While results remained unaffected when controlling for BDI Several studies have suggested that negative emotions may have a causal impact on the occurrence of binge eating [1][2][3][4][5] in binge eating disorder (BED). Furthermore, emotion regulation (ER) is known to influence the course of emotional experience [6,7] , and there is some evidence of ER deficits in BED patients [8,9] . We therefore tested the causal role of ER as a mediator in the link between negative emotions and desire to binge (DTB).…”
mentioning
confidence: 99%
“…Further significant differences were found between laxative abusers and non-abusers and between physically abused and the non-abused participants [17]. Binge eating disorders patients with alexithymia reported higher scores on BAT than nonalexithymia [18]. The BAT is also a good predictor of dissociative experiences and global therapy outcome [15].…”
Section: Methodsmentioning
confidence: 96%
“…There are independent subscales for anxiety and depression. Scores on each scale can be interpreted in ranges: normal (0-7), mild (8-10), moderate (11)(12)(13)(14) and severe (15)(16)(17)(18)(19)(20)(21). The HADS is considered to be reliable and valid measure of anxiety and depression.…”
Section: Methodsmentioning
confidence: 99%